Corrosion-resistant plant-growing concrete for ecological slope protection and preparation method of corrosion-resistant plant-growing concrete

By adopting a multifunctional composite material system and graded pore design in planted concrete, combined with self-repair functional materials, the shortcomings of existing planted concrete in high-salt, high humidity and high corrosion environments are solved, and the material's efficient corrosion resistance and ecological adaptability are achieved.

CN119912229APending Publication Date: 2025-05-02GUANGXI TRANSPORTATION VOCATIONAL & TECH COLLEGE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510146724.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When used in high-salt, high-humidity and high-corrosion marine environments, existing plant concrete lacks material performance, limited planting function, poor corrosion resistance and lack of self-repair ability, making it difficult to be used effectively in complex marine environments for a long time.

Method used

Low-thermal slag cement, metakaolin and microsilicon powder are used as the main cementitious materials, combined with the active blend of fly ash and natural zeolite powder, as well as reinforcement agents such as polymeric aluminum silicate, carbon nanotube-graphene composite materials and magnesium silicate powder, to form a multifunctional composite material system, and through graded pore design and introduction of microcapsules coated with calcium carbonate and other self-healing functional materials, optimize phytogenesis and corrosion resistance.

Benefits of technology

It significantly improves the chlorine corrosion resistance, crack resistance and ecological adaptability of phytochrome concrete, realizes the long-term durability and ecological restoration functions of materials in high-salt environments, and reduces maintenance costs and structural failure risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912229A_ABST
    Figure CN119912229A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ecological materials, and discloses a corrosion-resistant ecological slope protection vegetation concrete and a preparation method thereof.According to the concrete, low-heat slag cement, metakaolin, silica fume and an active admixture are synergistically optimized, and a reinforcing agent, a self-repairing material and vegetation function optimization components are combined; the chlorine salt corrosion resistance, the crack resistance and the vegetation ability of the material are improved. By adopting a multi-scale pore optimization technology, reasonable distribution of micropores, mesopores and macropores is realized, and the strength and vegetation stability of the concrete are improved. By introducing materials such as microcapsule coated calcium carbonate, cracks are automatically healed, and the service life of the material is prolonged. Meanwhile, environment-friendly materials such as fly ash and biochar are utilized, so that carbon emission and cost are reduced. The composite material has corrosion resistance, ecological property and environmental protection property, and is suitable for engineering protection and ecological restoration in a complex marine environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ecological materials, in particular to a kind of vegetative concrete for corrosion-resistant ecological slope protection and a preparation method thereof. Background Art

[0002] As a material that combines engineering protection and ecological restoration functions, vegetated concrete has received extensive attention in the fields of coastal protection and ecological environment restoration in recent years. However, the application of vegetated concrete in complex marine environments still faces many technical challenges, which are mainly reflected in material properties, vegetative capacity, corrosion resistance and environmental protection characteristics. Although there are some attempts to improve vegetated concrete in the existing technology, there are still obvious deficiencies in coping with the high-salt, high-humidity, high-corrosion environment of the coast and the coordinated optimization of ecological functions.

[0003] Insufficient material properties and pore structure design:

[0004] Existing concrete formulas usually use a single cementitious material or a simple combination of aggregates and additives. This design makes it difficult to balance the strength, corrosion resistance and ecological functions of the material. Specifically:

[0005] Lack of synergy in material formulation: The existing technology mainly uses ordinary silicate cement as the cementitious material, and the pore structure produced during its hardening process is uneven, resulting in insufficient resistance to chloride ion corrosion in high-salt environments. In addition, although admixtures such as fly ash and slag have certain applications, their role is often limited to improving strength, and their effects on optimizing pore structure and improving ecological functions are limited.

[0006] Self-repair function missing:

[0007] In the marine environment, vegetation concrete is subjected to external forces such as wind and wave impact, salt spray corrosion, and freeze-thaw cycles for a long time, which easily causes cracks. The existing solutions for crack repair mainly rely on external repair, which is inefficient and costly:

[0008] Lack of dynamic self-healing ability: Traditional bioreinforced concrete cannot achieve automatic healing of cracks. Self-healing functional materials are not introduced into the material. Once cracks are formed, they easily become penetration channels for chloride ions and water, leading to aggravated internal corrosion.

[0009] Insufficient control over crack expansion: Existing green concrete often experiences a rapid drop in strength or even failure after crack expansion, which is closely related to the lack of crystal filling and chemical anchoring capabilities within the material.

[0010] Vegetation function is limited:

[0011] One of the core of green concrete is to provide a suitable environment for plant growth. However, in the existing technology, the green performance of green concrete is obviously insufficient in high-salt environment:

[0012] Unbalanced nutrient supply: Existing green concrete rarely has a slow-release nutrient system. Plant roots have difficulty absorbing continuous nutrient support in a high-salt environment, resulting in low plant germination and survival rates.

[0013] Insufficient water retention capacity: Traditional concrete pores have difficulty locking in moisture, especially in salt spray environments, where moisture is easily absorbed by high salinity, further exacerbating plant growth stress.

[0014] Weak root adhesion: Due to the unreasonable pore design, it is difficult for plant roots to penetrate deeply into the material and stably attach, especially under the impact of wind and waves, they are easy to fall off, and the vegetation function cannot be maintained for a long time.

[0015] Therefore, the present invention proposes a corrosion-resistant ecological slope protection vegetation concrete and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention

[0016] In view of the shortcomings of existing vegetation concrete in terms of material properties, pore structure, self-repair ability and vegetation function, the present invention provides a corrosion-resistant vegetation concrete for ecological slope protection and a preparation method thereof, aiming to solve the application problems of materials in complex marine environments such as high salt, high humidity and high corrosion, while achieving the dual goals of ecological restoration and environmental protection.

[0017] To achieve the above objectives, the present invention is implemented through the following technical solutions: a kind of vegetative concrete for corrosion-resistant ecological slope protection, the vegetative concrete comprises the following raw materials in percentage:

[0018] Main cementitious material: 68-85%,

[0019] Active admixture: 13-25%,

[0020] Enhancer: 5-10%,

[0021] Plant growth function optimization ingredients: 2-6%,

[0022] Self-healing functional materials: 2-5%,

[0023] Aggregates and auxiliary components: 5-15%.

[0024] Preferably, the main gelling material is composed of the following raw materials in percentages:

[0025] Low-heat slag cement: 50-70%;

[0026] Metakaolin: 10-25%;

[0027] Microsilica fume: 8-15%.

[0028] Preferably, the active admixture is composed of the following percentages of raw materials:

[0029] Fly ash: 8-15%;

[0030] Natural zeolite powder: 5-12%;

[0031] Wherein, the particle size of the fly ash is 1-10 microns, and the particle size of the natural zeolite powder is 1-5 microns.

[0032] Preferably, the reinforcing agent is composed of the following percentages of raw materials:

[0033] Polyaluminium silicate: 2-5%;

[0034] Carbon nanotube-graphene composite material: 0.5-2%;

[0035] Magnesium silicate powder: 3-6%;

[0036] The dispersion of the carbon nanotube-graphene composite material is prepared by ultrasonic dispersion, the ultrasonic frequency is 40-60 kHz, and the dispersion time is 30-45 minutes.

[0037] Preferably, the vegetation function optimizing component is composed of the following percentages of raw materials:

[0038] Nitrogen, phosphorus and potassium slow-release granules: 0.5-2%;

[0039] Biochar nanoparticles: 0.5-3%;

[0040] Sodium alginate-based composite hydrogel: 0.3-1.5%;

[0041] The sodium alginate-based composite hydrogel has a water absorption rate of 5-10 times and is evenly dispersed in the concrete matrix.

[0042] Preferably, the self-repairing functional material is composed of the following raw materials in percentages:

[0043] Microcapsule coated calcium carbonate: 1-3%,

[0044] Calcium sulphoaluminate: 0.5-1.5%,

[0045] Alkaline activator: 0.5-3%.

[0046] Preferably, the aggregate and auxiliary components are composed of the following percentages of raw materials:

[0047] Porous ceramsite aggregate: 5-15%,

[0048] Air entraining agent: 0.02-0.1%,

[0049] Preservatives: 0.1-0.5%.

[0050] Preferably, a method for preparing a corrosion-resistant ecological slope protection vegetation concrete comprises the following steps:

[0051] S1. Material pretreatment:

[0052] Mix natural zeolite powder and magnesium silicate powder in a ratio of 1:1, dry at 100-120°C for 2-3 hours, and grind to a particle size of 1-5 microns;

[0053] The carbon nanotubes and graphene powders are mixed in a ratio of 1:1, deionized water is added to form a dispersion, and a 40-60 kHz ultrasonic disperser is used to disperse for 30-45 minutes to prepare a uniform dispersion;

[0054] S1. Mixing ingredients:

[0055] Dry mix the low-heat slag cement, metakaolin and microsilica powder in the main cementitious material in proportion, and stir at a speed of 60-80 rpm for 2-3 minutes;

[0056] Add fly ash and pretreated natural zeolite powder in the active admixture and continue dry mixing for 2-3 minutes;

[0057] Add the carbon nanotube-graphene dispersion and the polyaluminium silicate solution, and stir at a high speed of 300-500 rpm for 4-6 minutes to form a uniform slurry;

[0058] Add the vegetation function optimization ingredients and self-repairing functional materials, and stir at a low speed of 60-80 rpm for 2-3 minutes;

[0059] S3, pouring and molding:

[0060] The mixture is injected into a mold with a pore design of 5-10 mm in diameter and a pore density of 10-15 pores / m 2 ;

[0061] Perform vacuum degassing for 3-5 minutes under negative pressure of -0.08-0.1MPa to reduce internal bubbles and improve compactness.

[0062] S4. Maintenance:

[0063] Wet heat curing: in an environment of 50-60℃, humidity is controlled at 85-95%, curing for 3-5 days;

[0064] Salt spray curing: Place the concrete in a salt spray environment with a sodium chloride concentration of 5-10% for 14-28 days.

[0065] Preferably, in the material pretreatment step, the natural zeolite powder and magnesium silicate powder are ground into a particle size of 1-5 microns by a ball mill after drying, the rotation speed of the ball mill is 200-300 rpm, and the treatment time is 1-2 hours.

[0066] Preferably, in the casting and molding steps, the pores in the mold are formed by oil-water dispersion template technology, the oil-water dispersion ratio is 1:3-1:5, and the template is removed by heat treatment at 60-80°C or solvent elution after casting.

[0067] The present invention provides a kind of corrosion-resistant ecological slope protection vegetation concrete and its preparation method.

[0068] Beneficial effects:

[0069] 1. The present invention forms a multifunctional composite material system by using low-heat slag cement, metakaolin and microsilica as the main cementitious materials, supplemented by active admixtures of fly ash and natural zeolite powder, as well as an innovative combination of reinforcing agents such as polyaluminum silicate, carbon nanotube-graphene composite materials, and magnesium silicate powder. While ensuring basic strength, this system significantly improves resistance to chloride corrosion, cracking resistance and ecological adaptability. Vegetative concrete in the prior art is usually based on a single material or a simple combination, and it is difficult to achieve synergistic optimization of performance. Starting from the material basis, the technical solution of the present invention solves the problems of insufficient compatibility and single performance of the existing material system through functional division of labor and performance synergy, and reaches a new height of efficient composite functions.

[0070] 2. The present invention adopts a hierarchical pore design, specifically including a multi-scale distribution of micropores (<10μm), mesopores (10-100μm) and macropores (>100μm), wherein the micropores are filled with microsilica powder and air entraining agent to improve the anti-permeability, the mesopores provide good gas and water exchange through the combination of natural zeolite and fly ash, and the macropores provide stable support for the growth of plant roots through the optimization of porous ceramsite aggregate and template technology. Compared with the single-scale pore design in the prior art, it is easy to cause the contradiction between strength and function.

[0071] 3. The present invention innovatively introduces a self-healing functional material composed of microcapsules coated with calcium carbonate, calcium sulfoaluminate and alkaline activators into concrete. When cracks appear, the microcapsules automatically rupture to release active ingredients, which react with water and alkaline media in the environment to generate crystals to fill the cracks, thereby restoring the integrity and impermeability of the concrete. Compared with the prior art methods that rely on external crack repair, the present invention greatly reduces maintenance costs and structural failure risks by integrating a dynamic repair mechanism inside the material. In addition, concrete cracks in the prior art are often accelerated by corrosion failure due to the intrusion of external chloride ions. The present invention effectively solves the problem of insufficient corrosion resistance by automatically filling cracks and shielding corrosion pathways, thereby extending the service life of concrete in the marine environment.

[0072] 4. The present invention uses a large amount of industrial by-products and renewable materials in the formula design, such as fly ash, natural zeolite, biochar nanoparticles, etc., reducing the demand for the use of natural sand and stone materials. At the same time, the oil-water dispersion template technology is innovatively used to achieve multi-scale pore control during the casting process. The template agent is removed by heat treatment or solvent elution after casting, avoiding the high-energy consumption and high-pollution processing links in traditional processes. The present invention not only effectively reduces carbon emissions through the coordinated optimization of materials and processes, but also promotes the high-value utilization of industrial by-products, solves the problems of material unsustainability and resource waste in traditional technologies, and has significant environmental benefits and economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 The present invention is a flow chart of the preparation method of vegetated concrete suitable for coastal protection. DETAILED DESCRIPTION

[0074] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0075] Please refer to the attached Figure 1 :

[0076] Example:

[0077] Embodiment 1:

[0078] Materials preparation:

[0079] Low-heat slag cement (60%), metakaolin (20%) and microsilica powder (10%) were weighed in mass proportion as the main cementitious materials. Fly ash (10%) and natural zeolite powder (8%) were used as active admixtures. The natural zeolite powder was dried in advance and treated at 110°C for 2 hours and then ground to a particle size of 3 μm. Polyaluminium silicate (3%), carbon nanotube-graphene composite material (1%) and magnesium silicate powder (4%) were mixed in proportion for use. Slow-release particles (1%), biochar nanoparticles (2%) and sodium alginate-based composite hydrogel (0.8%) were weighed for use.

[0080] Dispersion and mixing:

[0081] Preparation of carbon nanotube-graphene dispersion: Add the composite material and deionized water in a ratio of 1:10 into an ultrasonic disperser with an ultrasonic frequency of 50 kHz for 40 minutes until the suspension is uniform and has no sedimentation.

[0082] In a mixer, dry mix the main gelling material at 70 rpm for 2 minutes, add the active admixture and continue stirring for 2 minutes, then pour in the carbon nanotube-graphene dispersion, increase the speed to 400 rpm and stir for 4 minutes. Finally, add the reinforcing agent, the vegetation function optimization component and the self-repairing material, and stir at a low speed of 60 rpm for 2 minutes.

[0083] Casting and molding:

[0084] The mixture is injected into a mold with a template with a pore size of 8 mm, and the pore density of the template is controlled to be 12 / m 2 . Vacuum degassing treatment, with negative pressure maintained at -0.09MPa for 4 minutes, removes air bubbles and improves the density of concrete.

[0085] Maintenance treatment:

[0086] Moist heat curing: The concrete is placed in a curing environment at 60°C and 90% humidity for 5 days.

[0087] Salt spray curing: Move the concrete blocks into a salt spray chamber with a sodium chloride concentration of 8% and continue curing for 21 days.

[0088] Embodiment 2:

[0089] Raw material handling:

[0090] Fly ash (15%) and natural zeolite powder (10%) are prepared in proportion. The natural zeolite powder is dried at 120°C for 3 hours and then ground to a particle size of 4 μm for later use. Low-heat slag cement (55%), metakaolin (25%), and microsilica powder (10%) are used as the main cementitious materials in proportion for later use.

[0091] Preparation of dispersion:

[0092] The carbon nanotubes and graphene were mixed in a ratio of 1:1, and deionized water was added to form a dispersion. The ultrasonic frequency was 60 kHz and the dispersion time was 35 minutes.

[0093] Mixing and forming:

[0094] The main cementitious material and the active admixture are dry mixed in a mixer at 75 rpm for 3 minutes. Pour the dispersion and polyaluminium silicate (4%), increase the speed to 450 rpm and stir for 5 minutes. Finally, add slow-release fertilizer particles (2%), microcapsule-coated calcium carbonate (2.5%) and porous ceramsite aggregate (10%), and stir at a low speed of 80 rpm for 3 minutes. Pour the slurry into a mold with an oil-water template with an oil-water ratio of 1:4. After pouring, the template is removed by heat treatment at 70°C.

[0095] Maintenance stage:

[0096] The wet heat curing conditions are 55°C and 95% humidity for 4 days. The salt spray curing environment has a sodium chloride concentration of 10% for 28 days.

[0097] Embodiment 3:

[0098] Raw materials preparation:

[0099] Low-heat slag cement (60%), metakaolin (20%), and microsilica powder (15%) are used as the main cementitious materials. Fly ash accounts for 10% and natural zeolite powder accounts for 7% of the active admixtures, and both are ground to less than 4μm.

[0100] Self-repairing functional components:

[0101] Microcapsule coated calcium carbonate (2%) and calcium sulfoaluminate (1%) were weighed separately and added to the main gelling material for dry mixing. Alkaline activator (2.5%) was added in liquid form during the stirring stage.

[0102] Mixing and pouring:

[0103] All dry mixed components were stirred at 80 rpm for 2 minutes, and the carbon nanotube dispersion was poured in and stirred at 300 rpm for 5 minutes. After completion, the slurry was poured into a mold with a pore size of 5 mm. The voids were eliminated by vacuum degassing (negative pressure -0.08 MPa, time 4 minutes).

[0104] Crack formation and repair:

[0105] After pouring, the concrete block was cured in a hot and humid environment (60°C, 90% humidity) for 7 days, and then cracks were created by artificial mechanical means. The crack width was controlled below 0.3 mm. The sample was placed in a salt spray curing box with a sodium chloride concentration of 5% and cured for 21 days. A large number of filling crystals were generated at the cracks.

[0106] Embodiment 4:

[0107] Material selection:

[0108] Low-heat slag cement (58%), kaolin (18%) and microsilica powder (12%) are used as the main cementitious materials. The active admixtures include fly ash accounting for 13% and natural zeolite powder accounting for 8%, both of which are industrial by-products.

[0109] Optimization of vegetation function:

[0110] Nitrogen, phosphorus and potassium slow-release particles (1.5%), biochar nanoparticles (2.5%), and sodium alginate-based composite hydrogel (1%) were added, and porous ceramsite was used as aggregate, with a ratio of 12%.

[0111] Formwork forming and maintenance:

[0112] Oil-water template molding, oil-water ratio is 1:5, the template agent is removed after solvent elution at 60℃, the wet heat curing conditions are 55℃, humidity 90%, time is 5 days, and salt spray curing lasts for 14 days.

[0113] Embodiment 5:

[0114] Recipe ratio:

[0115] Among the main cementitious materials, low-heat slag cement accounts for 65%, kaolin accounts for 15%, and microsilica accounts for 10%. In the active admixtures, the ratio of fly ash to natural zeolite powder is 12:8, and in the reinforcing agent, polyaluminum silicate accounts for 3.5% and carbon nanotube composite materials account for 1.5%.

[0116] Enhanced Mixing Process:

[0117] The stirring speed was 80 rpm during the dry mixing stage. After the carbon nanotube dispersion was added, the speed was increased to 500 rpm and stirred for 6 minutes. After the stirring was completed, the mixture was poured into a mold with a pore size of 6 mm.

[0118] Maintenance conditions:

[0119] The wet heat curing time is 6 days, the temperature is 50℃, the humidity is 95%, the salt spray curing sodium chloride concentration is 10%, and the time is 28 days.

[0120] Comparative Example:

[0121] Comparative Example 1: Comparison with Example 1 (Adjustment of the ratio of the main cementitious material)

[0122] Differences:

[0123] The proportion of kaolin in the main cementitious material is reduced to 5%, the proportion of microsilica powder is increased to 20%, and the other raw materials and process parameters remain the same as in Example 1.

[0124] Specific process:

[0125] Materials preparation:

[0126] Low heat slag cement: 60%; Kaolin: 5%; Microsilica fume: 20%;

[0127] Fly ash: 10%; natural zeolite powder: 8%.

[0128] Mixing and pouring:

[0129] Dry mixing, dispersion preparation, wet mixing and casting were carried out according to the steps of Example 1.

[0130] The inner hole diameter of the mold is 8mm, and the pore density is 12 / m 2 , vacuum degassing negative pressure is -0.09MPa, time is 4 minutes.

[0131] Maintenance treatment:

[0132] Moist heat curing conditions: 60℃, 90% humidity, curing for 5 days.

[0133] Salt spray curing conditions: sodium chloride concentration 8%, curing for 21 days.

[0134] Comparative Example 2: Comparison with Example 2 (the particle size of the zeolite powder in the active admixture is too large)

[0135] Differences:

[0136] The particle size of the natural zeolite powder was adjusted from 1-5 μm to 30 μm, and the proportions of other raw materials were consistent with those in Example 2.

[0137] Specific process:

[0138] Materials preparation:

[0139] Main cementitious materials: low-heat slag cement (55%), kaolin (25%), and microsilica fume (10%).

[0140] Active admixtures: fly ash (15%), natural zeolite powder (10%, particle size 30 μm).

[0141] Dispersion preparation:

[0142] The carbon nanotube-graphene dispersion was prepared according to the ultrasonic dispersion process of Example 2.

[0143] Mixing and forming:

[0144] Dry mixing, wet mixing and molding were carried out according to the mixing steps of Example 2.

[0145] After pouring, the formwork is removed by heat treatment at 70°C.

[0146] Maintenance treatment:

[0147] Moist heat curing conditions: 55℃, humidity 95%, curing for 4 days.

[0148] Salt spray curing conditions: sodium chloride concentration 10%, curing for 28 days.

[0149] Comparative Example 3: Comparison with Example 3 (without self-repairing functional material)

[0150] Differences:

[0151] The self-repairing functional materials (microcapsule-encapsulated calcium carbonate, calcium sulfoaluminate, and alkaline activator) are completely removed from the formula, and the proportions of the remaining materials are consistent with those in Example 3.

[0152] Specific process:

[0153] Materials preparation:

[0154] The ratio of the main cementitious material to the active admixture is consistent with that in Example 3.

[0155] The enhancer and vegetation function optimization ingredients remain unchanged, and no self-repairing functional materials are added.

[0156] Mixing and forming:

[0157] Dry mixing, dispersion preparation and wet mixing were carried out according to the process of Example 3.

[0158] After pouring, the inner hole diameter of the mold is 5mm, the vacuum degassing negative pressure is -0.08MPa, and the time is 4 minutes.

[0159] Maintenance treatment:

[0160] Moist heat curing conditions: 60℃, 90% humidity, curing for 7 days.

[0161] Salt spray curing conditions: sodium chloride concentration 5%, curing for 21 days.

[0162] Comparative Example 4: Comparison with Example 4 (without using green environmentally friendly materials)

[0163] Differences:

[0164] No industrial by-products such as fly ash and biochar nanoparticles are used at all. Instead, ordinary Portland cement is used as the main material, and ordinary aggregates replace porous expanded clay aggregates.

[0165] Specific process:

[0166] Materials preparation:

[0167] Ordinary Portland cement: 60%, kaolin: 20%, microsilica: 10%.

[0168] Active admixtures: fly ash and zeolite powder are completely replaced by sand and gravel aggregate (total amount 15%).

[0169] Eliminate the biochar and slow-release particles in the vegetation function optimization composition.

[0170] Mixing and forming:

[0171] Dry mix the main material with common aggregate for 3 minutes.

[0172] Add polyaluminium silicate and dispersion and stir at 400 rpm for 5 minutes.

[0173] After pouring, it is directly solidified and formed without the use of oil-water formwork.

[0174] Maintenance treatment:

[0175] Moist heat curing conditions: 60℃, 80% humidity, curing for 3 days.

[0176] Salt spray curing conditions: sodium chloride concentration 10%, curing for 14 days.

[0177] Comparative Example 5: Comparison with Example 5 (Pore Optimization Template Technology Not Used)

[0178] Differences:

[0179] Instead of using oil-water template technology for pore optimization, direct molding is used and no pores are designed inside the mold.

[0180] Specific process:

[0181] Materials preparation:

[0182] Prepare all materials according to the recipe ratio of Example 5.

[0183] It includes low-heat slag cement (65%), kaolin (15%), microsilica powder (10%), fly ash (12%), and natural zeolite powder (8%).

[0184] Mixing and forming:

[0185] In the dry mixing stage, stirring was performed at 80 rpm for 3 minutes. In the wet mixing stage, reinforcing agents and functional materials were added and the speed was increased to 450 rpm for stirring for 6 minutes.

[0186] The slurry is poured directly into a non-porous mold without using oil-water template technology.

[0187] Maintenance treatment:

[0188] Moist heat curing conditions: 50℃, 90% humidity, curing for 5 days.

[0189] Salt spray curing conditions: sodium chloride concentration 10%, curing for 28 days.

[0190] Test experiment:

[0191] Experiment 1:

[0192] Experimental objectives:

[0193] The ability of the bioreinforced concrete to resist chloride corrosion in a high-salt environment was tested, and the performance differences between the embodiments and the comparative examples were compared to verify the role of material optimization in improving corrosion resistance.

[0194] Experimental steps:

[0195] Sample preparation:

[0196] Cylindrical concrete specimens with a size of Φ100×50mm were prepared, and the following groups were selected:

[0197] Example 1 (optimized standard ratio and perfect pore design);

[0198] Example 2 (Optimal design of particle size of active admixture);

[0199] Comparative Example 1 (the ratio of the main cementitious material is unreasonable, and the proportion of kaolin is too low);

[0200] Comparative Example 2 (the particle size of natural zeolite powder is relatively large, reaching 30 μm) 10 samples were prepared in each group and subjected to wet heat curing at room temperature for 28 days.

[0201] Experimental methods:

[0202] Rapid Chloride Penetration Test (RCPT) according to ASTM C1202 standard:

[0203] Epoxy resin was coated on the upper and lower surfaces of each sample to form a sealed cell, with only two side surfaces exposed for penetration testing.

[0204] Immerse in 3.5% sodium chloride solution, power on at 60V for 6 hours.

[0205] The current during the power-on period of each sample was recorded, and the amount of charge passing through the sample (in coulombs) was calculated by integration.

[0206] Experimental conditions:

[0207] Sodium chloride solution concentration: 3.5%

[0208] Power supply voltage: 60V

[0209] Test time: 6 hours

[0210] Experimental temperature: room temperature (25±2℃)

[0211] Data recording and organization:

[0212] The coulomb value of each group of samples was recorded, the average value was calculated, and the results were used for comparative analysis.

[0213] Experimental data:

[0214] Table 1: Coulomb value test results of chloride corrosion resistance

[0215]

[0216] From the data results of this experiment, it can be seen that the coulomb value of the embodiment is significantly lower than that of the comparative example, which indicates that the optimized vegetation concrete has a stronger resistance to chloride ion penetration in a high-salt environment. Example 1 performed particularly well, with the lowest charge, indicating that the synergistic effect of pore structure design and material ratio effectively reduced the penetration path of chloride ions. This is highly consistent with the multi-scale pore optimization theory: micropores increase density, mesopores regulate internal moisture migration, and macropores provide a stable foundation for external vegetation while avoiding overall strength loss.

[0217] The performance of Example 2 is inferior to that of Example 1, but still better than that of the comparative example. The optimization of the particle size of the zeolite powder plays a key role. Through the reaction of the higher specific surface area with the cement matrix, the adsorption and fixation capacity of chloride ions is increased. However, the particle size of the zeolite powder in Comparative Example 2 is too large, and its physical adsorption and chemical shielding effects cannot be fully exerted, resulting in a significant increase in the chloride salt corrosion path. This shows that particle size control is crucial to achieving the chloride salt resistance of the material.

[0218] The data of comparative example 1 further proves that the adjustment of the ratio of the main cementitious material has a significant impact on the chloride resistance performance. The low proportion of kaolin leads to a significant decrease in the density of the concrete matrix and an increase in microcracks, thereby weakening the shielding effect of the pores. This phenomenon can be explained from the chemical anchoring theory of the material: the lack of secondary hydration reaction involving kaolin makes it impossible for the matrix structure to form a high-density CSH gel, thereby providing a channel for chloride ion penetration.

[0219] Experiment 1 not only verifies the scientific nature of the material optimization of the embodiment, but also reveals the root cause of the insufficient material performance in the prior art. The optimized material system and process provide a reliable solution for anti-chloride salt corrosion, especially showing significant advantages in high-salt environments.

[0220] Experiment 2:

[0221] Experimental objectives:

[0222] The self-repairing ability of the cracks was tested, and the effect of the self-repairing functional material was verified by observing the changes in the crack healing rate and the anti-permeability, and the performance differences between Example 3 and Comparative Example 3 were compared.

[0223] Experimental steps:

[0224] Sample preparation:

[0225] Prepare prismatic specimens with dimensions of 40×40×160 mm, and select the following groups:

[0226] Example 3 (containing self-repairing functional materials: microcapsule-encapsulated calcium carbonate, calcium sulfoaluminate, and alkaline activator).

[0227] Comparative Example 3 (without adding any self-repairing functional material).

[0228] Ten samples were prepared for each group and cured in moist heat at room temperature for 28 days.

[0229] Crack creation:

[0230] The three-point loading method was used to apply a concentrated load to the center of the specimen and control the crack width to 0.3 mm. During the loading process, a crack microscope was used to monitor the crack width in real time to ensure that the crack was controlled within the set range.

[0231] All specimens after crack creation were photographed and the initial crack morphology was recorded.

[0232] Maintenance settings:

[0233] The crack specimens were immersed in saturated Ca(OH)2 solution and cured for 28 days at a curing temperature of 25±2℃. The solution was replaced once a week.

[0234] Crack healing observation:

[0235] Use a crack microscope to observe crack changes and record the reduction in crack width.

[0236] The crack healing rate is calculated according to the following formula:

[0237]

[0238] Anti-penetration performance test:

[0239] After the crack healing and maintenance is completed, a water pressure penetration test is carried out.

[0240] Apply 0.5MPa water pressure to the bottom of the sample, test the amount of water penetration and penetration depth, and record the data.

[0241] Experimental data:

[0242] Table 2: Crack self-repair ability test results

[0243]

[0244]

[0245] The experimental results clearly show the performance difference between the examples and the comparative examples. In Example 3, the crack healing rate was significantly higher than that of Comparative Example 3, reaching an average of 91.3%, while that of Comparative Example 3 was only 13.4%. This shows that self-healing functional materials play an important role in the spontaneous healing process after cracks are generated. Microcapsule-coated calcium carbonate releases active ingredients when cracks are formed, reacts with hydrates to form calcium carbonate crystals, fills the cracks, and restores the integrity of the matrix. Mechanistically, this dynamic crack repair conforms to the theory of chemical anchoring and crystal deposition, and prevents further water penetration by actively healing cracks.

[0246] From the perspective of anti-penetration performance, the penetration depth of Example 3 is significantly lower than that of Comparative Example 3, with an average value of only 10.7 mm, while the comparative example is as high as 23.6 mm. This performance difference mainly comes from the synergistic effect of calcium sulfoaluminate and alkaline activator added in the examples. When cracks appear, these materials promote the rapid generation of calcium sulfoaluminite and CSH gel, making the crystal filling efficiency in the cracks higher. However, Comparative Example 3 does not add any self-healing functional materials, and the cracks are always exposed, resulting in a significant increase in the penetration depth. This shows that crack healing can not only repair the surface, but also effectively reduce the internal permeation channels.

[0247] The data also show that the crack healing rate of Example 3 has certain fluctuations (88.5%-95.4%), which may be related to the crack morphology and uniformity of material distribution. This volatility further shows that the active substances released by the microcapsules need to rely on the morphological characteristics of the cracks and water penetration to trigger their reaction mechanism. Therefore, in practical applications, it is necessary to pay attention to the distribution of materials and the crack generation pattern to ensure the best performance of the self-healing function. The experimental results fully verify the technical advantages of the embodiment in the field of crack repair, and at the same time reveal the limitations of the comparative example in corrosion resistance design.

[0248] Experiment 3:

[0249] Experimental objectives:

[0250] The plant attachment ability and vegetation survival rate of the vegetation concrete were tested, and the performance difference between Example 4 and Comparative Example 4 was compared to verify the effect of the vegetation function optimization component in the marine high-salt environment.

[0251] Experimental steps:

[0252] Sample preparation:

[0253] Cylindrical vegetation concrete specimens with a size of Φ100×50mm were prepared, and the following groups were selected:

[0254] Example 4 (containing ingredients for optimizing plant growth functions: slow-release particles, biochar nanoparticles, and sodium alginate-based hydrogel).

[0255] Comparative Example 4 (without the vegetation function optimization component, only using ordinary Portland cement and aggregate) 10 samples were prepared in each group and maintained in wet heat for 28 days.

[0256] Planting preparation:

[0257] Fill the pores of the sample with nutrient matrix (peat soil and perlite mixed in a ratio of 1:1).

[0258] Arabidopsis seeds were planted, 50 seeds per sample.

[0259] Pour 50 mL of deionized water to saturate the pores.

[0260] Salt spray environment maintenance

[0261] The sample is placed in a salt spray curing box with the following environmental settings:

[0262] Sodium chloride concentration: 5%;

[0263] Temperature: 25℃;

[0264] Humidity: 90%;

[0265] Add 50 mL of deionized water every day and continue curing for 28 days.

[0266] Experimental observation and record:

[0267] The germination rate of the plants (number of germinated seeds / total number of seeds x 100%) was recorded every 7 days.

[0268] After 28 days of maintenance, the vegetation survival rate was measured (number of surviving plants / total number of germinations×100%).

[0269] The root adhesion (N) was measured using a root pull-out tester, and 5 samples were randomly selected from each group for testing.

[0270] Experimental data:

[0271] Table 3: Test results of vegetation performance of vegetated concrete

[0272]

[0273] The experimental results show that the vegetation concrete in Example 4 is superior to that in Comparative Example 4 in terms of germination rate, survival rate and root adhesion. The germination rate averaged 85.6%, while that of the comparative example was only 49.4%. This difference is mainly attributed to the slow-release particles and sodium alginate-based hydrogel added in Example 4. In a salt spray environment, the slow-release particles gradually release nitrogen, phosphorus and potassium nutrients, providing a stable source of nutrients for plant growth. The hydrogel reduces the impact of the high-salt environment on the germination of plant seeds by absorbing water and maintaining the moisture content in the pores. Comparative Example 4 lacks vegetation function optimization components, and it is difficult for plant roots to absorb sufficient nutrients, resulting in a significant decrease in the germination rate.

[0274] In terms of survival rate, Example 4 reached 80.4%, while the comparative example was only 35.8%. This shows that the marine salt spray environment has a significant survival pressure on plants, and the synergistic effect of the porous structure of Example 4 and the biochar particles successfully alleviated this pressure. The biochar particles absorb salt through their porous characteristics and provide attachment space for the roots, effectively reducing the direct damage of salt to the roots of plants. Comparative Example 4 uses ordinary Portland cement and sand and gravel aggregates, with a single pore structure and airtightness, and the accumulation of salt leads to extremely high plant mortality.

[0275] The test of root adhesion also further confirmed the advantages of Example 4. The average root adhesion was 0.76N, while the comparative example was only 0.21N. This is closely related to the pore design. The multi-scale pore structure of Example 4 provides a suitable growth space for plant roots, and the sodium alginate-based hydrogel fills the pores to form a flexible support system, allowing the roots to be deeply embedded and tightly attached. Due to the lack of optimized pore structure and functional materials in Comparative Example 4, the roots cannot penetrate deep into the aggregates, resulting in significantly insufficient adhesion.

[0276] The experiment not only reveals the ecological effects of the optimized materials in the embodiment, but also fully verifies the limitations of the comparative technical solution in terms of plant growth performance. This comparison fully reflects the technical innovation and superiority of the embodiment from the perspectives of structure, function and plant response.

[0277] Experiment 4:

[0278] Experimental objectives:

[0279] The green and environmentally friendly performance of the vegetation concrete was tested, and the carbon emissions and thermogravimetric analysis (TGA) were used to compare Example 4 with Comparative Example 4 to verify the role of the green and environmentally friendly materials in the present invention.

[0280] Experimental steps:

[0281] Sample preparation:

[0282] Prepare cubic specimens with a size of 50×50×50 mm, and select the following groups:

[0283] Example 4: Using green materials such as fly ash, biochar, and porous ceramsite;

[0284] Comparative Example 4: Traditional silicate cement and ordinary aggregate are used completely.

[0285] Ten specimens were prepared in each group and subjected to wet heat curing for 28 days.

[0286] Carbon emissions determination:

[0287] Calculate the percentage of green materials (fly ash, biochar, and expanded clay) in the total weight during the preparation of each group of samples.

[0288] According to ISO14067 standard, a carbon emission analyzer is used to test the carbon emissions (kgCO2-eq) per kilogram of sample during the manufacturing process.

[0289] Thermogravimetric analysis (TGA)

[0290] The thermal weight loss of the samples was tested below 800°C, and the mass loss in each temperature range was recorded using a thermogravimetric analyzer.

[0291] The proportion of recyclable components in the samples was analyzed, such as biochar and ceramsite ash content.

[0292] Cost Analysis:

[0293] The raw material cost of each set of samples was recorded to compare the economic efficiency of traditional materials and green materials.

[0294] Experimental data:

[0295] Table 4: Test results of green environmental performance of vegetation concrete

[0296]

[0297] The data reveals the significant advantages of Example 4 in terms of carbon emissions and resource recyclability. The average carbon emissions of Example 4 are 0.75 kgCO2-eq, which is significantly lower than 1.51 kgCO2-eq of Comparative Example 4. This is mainly due to the high proportion of fly ash and biochar in the example, which replaces part of the high-energy cement raw materials. As a renewable material, biochar absorbs a large amount of carbon dioxide during its production process, achieving negative carbon emissions. In addition, the use of porous ceramsite reduces the energy consumption of aggregate mining and processing, reducing the carbon footprint from the source. Comparative Example 4 uses all-Portland cement, which has high energy consumption and carbon emissions that are almost twice that of the example, fully exposing the environmental burden of traditional formulas.

[0298] Thermogravimetric analysis further supports the contribution of green materials in the examples. The average thermal weight loss of Example 4 is 18.84%, which is significantly higher than 9.1% of Comparative Example 4. This shows that the biochar and porous ceramsite in the examples not only improve the reuse value of the materials, but also improve the stability of the samples in high temperature environments. Specifically, the residual carbon content of biochar at high temperatures and the inorganic components in porous ceramsite can be recycled as renewable materials for other purposes. In Comparative Example 4, the silicate cement has almost no renewable components after high-temperature decomposition, and the resource recovery rate is extremely low.

[0299] The economic analysis also highlights the potential value of the embodiment. The material cost of Example 4 is 4.56 yuan / kg on average, which is lower than 5.52 yuan / kg of Comparative Example 4. By introducing a high proportion of industrial waste (such as fly ash) and low-cost biochar, the embodiment reduces the overall material cost, while the high proportion of cement and sand and gravel materials in the comparative example leads to a high cost. This cost difference gives the embodiment a clear economic advantage in large-scale production and promotion.

[0300] The experimental summary fully verifies the significant advantages of the embodiment in terms of green environmental performance. These advantages come not only from the introduction of renewable materials in the formula, but also from the overall improvement of resource utilization by the optimized material system. The disadvantages of the comparative example in terms of environmental burden and cost structure further reflect the limitations of the traditional formula and also provide strong support for the application of the present invention in the field of environmental protection.

[0301] Experiment 5:

[0302] Experimental objectives:

[0303] The effect of pore structure optimization on the performance of bioreinforced concrete was tested, and the effectiveness of multi-scale pore design was verified by comparing Example 5 with Comparative Example 5 through tests on porosity, pore distribution and compressive strength.

[0304] Experimental steps:

[0305] Sample preparation:

[0306] Prepare cylindrical specimens with a size of Φ100×50mm and select the following groups:

[0307] Example 5: Pore optimization using oil-water dispersion template technology, pore diameter 510 mm, pore density 1015 pores / m 2 ;

[0308] Comparative Example 5: Pore optimization template technology was not used, direct molding was performed, and the pore structure was not optimized.

[0309] There are 10 samples in each group, and they are cured in wet heat for 28 days.

[0310] Porosity and pore distribution test:

[0311] The total porosity and pore distribution of the samples were tested using mercury intrusion porosimetry, and the proportions of micropores (<10 μm), mesopores (10-100 μm), and macropores (>100 μm) were recorded.

[0312] The test pressure range is 0.1-100MPa, and the volume proportion corresponding to each pore diameter is recorded.

[0313] Compressive strength test:

[0314] The compressive strength test is carried out in accordance with GB / T50081-2019 standard.

[0315] An electronic universal testing machine was used with a loading rate of 0.5 MPa / s to record the maximum breaking load of the specimen.

[0316] Data Records:

[0317] The porosity, pore distribution and compressive strength of the two groups of samples were recorded respectively.

[0318] Experimental data:

[0319] Table 5: Pore structure optimization and compressive strength test results

[0320]

[0321] Experimental data show that multi-scale pore optimization has a significant impact on the mechanical properties and pore distribution of bioremediation concrete. The total porosity of Example 5 is 19.5%, which is much lower than the 28.4% of Comparative Example 5, indicating that the formation of large pores is reduced by the oil-water template technology, and the pore structure is significantly optimized. Mechanistically, the increase in the proportion of micropores and mesopores enhances the matrix density of the concrete, reduces pore connectivity, and significantly reduces the presence of stress concentration areas, thereby improving the overall compressive strength.

[0322] The comparison of pore distribution further illustrates the advantages of multi-scale pore design. In Example 5, the proportion of micropores and mesopores totaled 77.3%, while that of the comparative example was only 59.5%. This difference shows that the example rationally distributed the pore structure through template technology and avoided excessive aggregation of macropores (>100μm). Macropores accounted for as much as 40.5% in the comparative example, which directly led to an increase in pore connectivity, which not only reduced the compressive strength, but also provided a path for crack expansion, significantly weakening the corrosion resistance of the material.

[0323] The compressive strength test results clearly reflect the influence of pore structure on mechanical properties. The average compressive strength of Example 5 is 52.5MPa, which is 44% higher than that of Comparative Example 5. The optimized pore structure improves the ability of the material to resist external loads by enhancing the uniformity and mechanical stability of the matrix. At the same time, the increase in micropores provides more generation space for hydration products, further improving the compactness of concrete. However, due to the presence of large pores, Comparative Example 5 has insufficient stress dispersion ability and is ultimately destroyed with a lower strength value, showing the limitations of traditional molding processes.

[0324] The multi-scale pore design combined with the pore optimization template technology improves the compactness, strength and long-term corrosion resistance of concrete from a mechanistic point of view. This structural optimization not only shows significant performance advantages in experiments, but also provides reliable technical support for practical engineering applications. The comparative data further proves that the traditional process cannot take into account both pore regulation and material performance, which reflects the creativity and applicability of the technology of the present invention.

[0325] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A kind of vegetative concrete for corrosion-resistant ecological slope protection, characterized in that: The biodegradable concrete comprises the following raw materials: Main cementitious material: 68-85%, Active admixture: 13-25%, Enhancer: 5-10%, Plant growth function optimization ingredients: 2-6%, Self-healing functional materials: 2-5%, Aggregates and auxiliary components: 5-15%.

2. The anti-corrosion ecological slope protection vegetative concrete according to claim 1 is characterized in that: The main cementitious material is composed of the following raw materials in the following percentages: Low-heat slag cement: 50-70%; Metakaolin: 10-25%; Microsilica fume: 8-15%.

3. The anti-corrosion ecological slope protection vegetation concrete according to claim 1 is characterized in that: The active admixture is composed of the following raw materials in the following percentages: Fly ash: 8-15%; Natural zeolite powder: 5-12%; Wherein, the particle size of the fly ash is 1-10 microns, and the particle size of the natural zeolite powder is 1-5 microns.

4. The anti-corrosion ecological slope protection vegetation concrete according to claim 1 is characterized in that: The reinforcing agent is composed of the following raw materials in the following percentages: Polyaluminium silicate: 2-5%; Carbon nanotube-graphene composite material: 0.5-2%; Magnesium silicate powder: 3-6%; The dispersion of the carbon nanotube-graphene composite material is prepared by ultrasonic dispersion, the ultrasonic frequency is 40-60 kHz, and the dispersion time is 30-45 minutes.

5. The anti-corrosion ecological slope protection vegetative concrete according to claim 1 is characterized in that: The vegetation function optimization component is composed of the following raw materials in the following percentages: Nitrogen, phosphorus and potassium slow-release granules: 0.5-2%; Biochar nanoparticles: 0.5-3%; Sodium alginate-based composite hydrogel: 0.3-1.5%; The sodium alginate-based composite hydrogel has a water absorption rate of 5-10 times and is evenly dispersed in the concrete matrix.

6. The anti-corrosion ecological slope protection vegetative concrete according to claim 1, characterized in that: The self-repairing functional material is composed of the following raw materials in percentage: Microcapsule coated calcium carbonate: 1-3%, Calcium sulphoaluminate: 0.5-1.5%, Alkaline activator: 0.5-3%.

7. The anti-corrosion ecological slope protection vegetative concrete according to claim 1 is characterized in that: The aggregate and auxiliary components are composed of the following percentages of raw materials composition: Porous ceramsite aggregate: 5-15%, Air entraining agent: 0.02-0.1%, Preservatives: 0.1-0.5%.

8. The method for preparing the corrosion-resistant ecological slope protection vegetation concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Material pretreatment: Mix natural zeolite powder and magnesium silicate powder in a ratio of 1:1, dry at 100-120°C for 2-3 hours, and grind to a particle size of 1-5 microns; The carbon nanotubes and graphene powders are mixed in a ratio of 1:1, deionized water is added to form a dispersion, and a 40-60 kHz ultrasonic disperser is used to disperse for 30-45 minutes to prepare a uniform dispersion; S1. Mixing ingredients: Dry mix the low-heat slag cement, metakaolin and microsilica powder in the main cementitious material in proportion, and stir at a speed of 60-80 rpm for 2-3 minutes; Add fly ash and pretreated natural zeolite powder in the active admixture and continue dry mixing for 2-3 minutes; Add the carbon nanotube-graphene dispersion and the polyaluminium silicate solution, and stir at a high speed of 300-500 rpm for 4-6 minutes to form a uniform slurry; Add the vegetation function optimization ingredients and self-repairing functional materials, and stir at a low speed of 60-80 rpm for 2-3 minutes; S3, pouring and molding: The mixture is injected into a mold with a pore design of 5-10 mm in diameter and a pore density of 10-15 pores / m 2 ; Perform vacuum degassing for 3-5 minutes under negative pressure of -0.08-0.1MPa to reduce internal bubbles and improve compactness. S4. Maintenance: Wet heat curing: in an environment of 50-60℃, humidity is controlled at 85-95%, curing for 3-5 days; Salt spray curing: Place the concrete in a salt spray environment with a sodium chloride concentration of 5-10% for 14-28 days.

9. The method for preparing a corrosion-resistant ecological slope protection vegetation concrete according to claim 8, characterized in that: In the material pretreatment step, the natural zeolite powder and magnesium silicate powder are ground into a particle size of 1-5 microns by a ball mill after drying. The rotation speed of the ball mill is 200-300 rpm and the treatment time is 1-2 hours.

10. The method for preparing the corrosion-resistant ecological slope protection vegetation concrete according to claim 8, characterized in that: The pore structure of the vegetation concrete includes: Micropores, with a pore size of less than 10 μm, are formed by filling with microsilica powder; Mesopores, with a pore size of 10-100 μm, are generated by the synergistic effect of air-entraining agent and natural zeolite powder; macropores, with a pore size of 100-500 μm, are formed by porous ceramsite aggregate and template design.

Citation Information

Cited By

  • Preparation method and application of magnesium vegetation concrete

    CN120864859A